Clinical, radiological, and functional evaluation of surgical treatment in degenerative lumbar canal stenosis - Jeswani, Mayank; Vivek Kumar Kankane; Avdhesh Shukla; Avinash Kumar; Avinash Sharma (Asian Journal of Medical Sciences, 2023)
Background: Low-back pain (LBP) is extremely prevalent and is the one of the most common causes for people to seek medical attention. As life expectancy continue to increase, prevalence of symptomatic spinal stenosis will increase. Although lumbar stenosis is not life-threatening, it can cause chronic and sustained pain and can limit activity severely. Early, accurate diagnosis, and treatment of lumbar stenosis is important in preserving activity in elderly population. Aims and Objectives: The study was conducted to find the incidence of degenerative lumbar canal stenosis (LCS) among patients of LBP, to evaluate clinicoradiological profile and to evaluate the outcome and complications in the surgically treated patients of degenerative LCS. Materials and Methods: This prospective study included all patients admitted with LCS under department of neurosurgery, GR medical college and associated J.A. group of Hospitals from December 2021 to December 2022 who underwent surgery. No randomization done. Results: Out of total 48 patients, 58% were males while 42% were females, 62.5% of patients were of more than 40 years of age, all patients were having LBP and 64.5% of patients were having LBP for the past 1 year. After surgical management, 87.5% of patients shows improvement in symptoms in Oswestry disability index and Visual analog scale scales. Conclusion: Overall good surgical outcome is obtained and better surgical results in degenerative LCS compared to other studies. Patients with degenerative LCS presenting with back pain and associated neurological deficit are successfully managed with surgical treatment in this study.